Need for stomatological treatment in children of the Special School "Jardín de La Alegría", 2016 - Deysi Suárez Zafra; Anisley Cabrera Salas; Isis Esther de la Torre Hernández; Gerardo Gilberto Estrada Sánchez (Editorial Ciencias Médicas, 2019)
Introduction: The oral health of the intellectually disabled patient has been a great concern worldwide. Cuba does not escape this concern by implementing programs that prioritize this type of individuals. Objective: To determine the need for stomatological treatment of patients with intellectual disability according to the diagnostic category of the Jardín de la Alegría Special School. Methods: a cross-sectional descriptive study conducted in the period 2016-2017. The clinical examination of the students was carried out in the dental chair. For the collection of the information a survey form was made taking into account the characteristics of the group under study: age, sex, diagnostic category, COP-D index and ceo-d, index of need for community periodontal treatment, and oral hygiene using the simplified oral hygiene index of Greene and Vermillon. The universe of study was constituted by 105 children that represents the total enrollment of the school. Results: the diagnostic category that prevailed was the mild intellectual disability with 82.8. 68.6% of the studied population presented regular oral hygiene. 67.6% of the children presented periodontal disease, 59.0% malocclusion and 54.2% dental caries. According to need of treatment, 67% need periodontal treatment, 59.0% orthodontic treatment and 45.7% need conservative treatment. Conclusions: there was a high need for periodontal treatment in individuals with mild intellectual disability.